Proceedings of the International Conference on the Renewal and Reform of Islamic Thought and Civilisation (ICRITC’24) - Ahmad, Khaliq; Norman, Nurul Ain; Berghout, Abdul Aziz (ISTAC-IIUM Publication 24, Persiaran Tuanku Syed Sirajuddin, Bukit Tunku, 50480 Kuala Lumpur Wilayah Persekutuan, 2024)
This book is a compilation of the papers presented at the International Conference on the Renewal and Reform of Islamic Thought and Civilisation, held ISTAC-IIUM from the 23-24 April 2024. The views expressed in these proceedings are those of the individual authors and do not necessarily reflect the views of the publisher or the conference organisers. First Edition-2024